The impact of extracellular osmolality on Saccharomyces yeast populations during brewing fermentations - Zhuang, Shiwen; Smart, Katherine; Powell, Chris (American Society of Brewing Chemists, 2017)
Osmotic stress represents one of the major environmental challenges experienced by yeast during industrial 15 fermentations. This stress is particularly associated with high gravity processes which utilise concentrated 16 substrates to yield products with elevated concentrations of ethanol. The aims of this work were to quantitatively 17 measure factors affecting extracellular osmotic pressure (osmolality) during brewing fermentations, and to 18 determine their effects on yeast at the physiological and molecular level. Osmolality was observed to increase 19 during fermentation due predominantly to ethanol production, indicating a strong relationship between these 20 environmental parameters. High osmolality was shown to have a negative impact on yeast physiology, viability 21 and vitality and although genome integrity was unaffected, cell membrane fluidity became altered. This data not 22 only demonstrates the occurrence of an increase in osmotic pressure during fermentation, but provides 23 explanation for the decrease in yeast quality typically observed under high gravity conditions. The results 24 presented here are directly relevant to all brewery fermentations worldwide and have applications within 25 associated industries where microorganisms are used for ethanol production, including food products, alcoholic 26 beverages and biofuels.